Attendance at cardiac rehabilitation is associated with lower all-cause mortality after 14 years of follow-up. Issue 9 (4th December 2012) - Beauchamp, Alison; Worcester, Marian; Ng, Andrew; Murphy, Barbara; Tatoulis, James; Grigg, Leeanne; Newman, Robert; Goble, Alan
Abstract : Objective: To investigate whether attendance at cardiac rehabilitation (CR) independently predicts all-cause mortality over 14 years and whether there is a dose–response relationship between the proportion of CR sessions attended and long-term mortality. Design: Retrospective cohort study. Setting: CR programmes in Victoria, Australia Patients: The sample comprised 544 men and women eligible for CR following myocardial infarction, coronary artery bypass surgery or percutaneous interventions. Participants were tracked 4 months after hospital discharge to ascertain CR attendance status. Main outcome measures: All-cause mortality at 14 years ascertained through linkage to the Australian National Death Index. Results: In total, 281 (52%) men and women attended at least one CR session. There were few significant differences between non-attenders and attenders. After adjustment for age, sex, diagnosis, employment, diabetes and family history, the mortality risk for non-attenders was 58% greater than for attenders (HR=1.58, 95% CI 1.16 to 2.15). Participants who attended <25% of sessions had a mortality risk more than twice that of participants attending ≥75% of sessions (OR=2.57, 95% CI 1.04 to 6.38). This association was attenuated after adjusting for current smoking (OR=2.06, 95% CI 0.80 to 5.29). Conclusions: This study provides further evidence for the long-term benefits of CR in a contemporary, heterogeneous population. While a dose–response relationship may exist between the number of sessions attended and long-term mortality, this relationship does not occur independently of smoking differences. CR practitioners should encourage smokers to attend CR and provide support for smoking cessation.